A Review of ERC Teacher Training Programs Across Nine Quebec Universities: A Snapshot 10 Years After 2008. Issue 3 (2nd September 2018) - Chan, Wing Yu Alice
Abstract: Although scholars have critiqued the Quebec Ethics and Religious Culture (ERC) program, few, if any, have reviewed ERC teacher training programs. To raise this discussion, a preliminary analysis of the ERC teacher training requirements across nine universities was conducted. Findings show that attention remains on the preparation of secondary over elementary teachers, that content courses are more prevalent than pedagogical courses, and that each university holds varying conceptions of the ERC course. Thus, some ERC training appears to limit the development of the dialogue competency and the time required for teachers to foster the self-awareness to teach the course neutrally.